The invisible engine: Legal Protections and Challenges for Migrant Workers in 2026 - Debalina Sengupta,; Chinmaya Mohapatra, (The Bioscan, 2026)
Migrant workers are still the pillar of the global economy, but they often live in a "legal twilight zone." By 2026, the scenario of migrant workers is rapidly changing because of upcoming regional agreements, digital surveillance, and proper implementation of long-awaited labour codes.